Development of a Digital Formative Assessment Instrument for Mathematics Learning in Secondary Education - Fadhila, Nurul (Aksioma Education Journal, 2024)
The rapid expansion of digital technology in education has highlighted the need for more adaptive and responsive formative assessment systems, particularly in secondary mathematics learning. This study aims to develop and validate a digital formative assessment instrument designed to support real-time monitoring, adaptive feedback, and data-driven decision-making. Employing a Research and Development approach using a modified 4D model (Define, Design, Develop, Disseminate), the instrument was systematically created and evaluated through expert validation, teacher and student practicality testing, classroom observations, interviews, and system log analysis. Quantitative data were analyzed using SPSS, including descriptive statistics, reliability testing with Cronbach’s Alpha, normality testing with Shapiro–Wilk, and effectiveness analysis using paired-sample t-tests. Results indicate that the instrument achieved high validity (mean = 4.62; α = 0.91), strong practicality among teachers (mean = 4.47) and students (mean = 4.58), and significant improvement in student outcomes (t = 8.214; p = 0.000). System log data further revealed increased accuracy, shorter completion times, and higher feedback interaction. These findings demonstrate that the digital formative assessment instrument is pedagogically robust, practically feasible, and effective in enhancing mathematics learning. Thus, the developed instrument successfully fulfills the research objective and offers a comprehensive solution for improving formative assessment practices in digital-era mathematics education.